Countdown : the blinding future of nuclear weapons - Scoles, Sarah (Bold Type Books, Hachette Book Group, 2024)
Nuclear weapons are, today, as important as they were during the Cold War. In fact, some experts say we could be as close to a nuclear catastrophe now as we were at the height of that conflict. Yet conversations about nuclear bombs generally happen in past tense. In Countdown, science journalist Sarah Scoles uncovers a different atomic reality: the unclear age's present. Drawing from years of on-the-ground reporting at the nation's nuclear weapons labs, Scoles interrogates the idea that having nuclear weapons keeps us safe, deters attacks, and prevents radioactive warfare. She deftly assesses the existing nuclear apparatus in the United States, taking readers beyond the news headlines and policy-speak to reveal the state of nuclear weapons technology, as well as how people currently working within the US nuclear weapons complex have come to think about these bombs. Through a sharp, surprising, and undoubtedly urgent narrative, Scoles brings us out of the Cold War and into the twenty-first century. She opens readers' eyes to the true nature of nuclear weapons and their caretakers while also giving us the context necessary to understand the consequences of their existence for worse and for better, for now and for the future. -- Dust jacket.